Injuries to the head, face, mouth and neck in physically abused children in a community setting - A. M. CAIRNS, J. Y. Q. MOK, & R. R. WELBURY (Paediatric Dentistry, 2005)
The aims of the present study were to identify the incidence of orofacial injuries found within a cohort of physically abused children, and examine demographic data surrounding the alleged perpetrator, the location in which the alleged assault occurred, the mechanism of injury and the actual orofacial injury incurred.